2022
DOI: 10.1186/s12868-022-00708-w
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of strength training in a neuroinflammatory animal model

Abstract: Background The preventive role of muscular strength on diminishing neuroinflammation is yet unknown. In this study, the role of the prophylactic muscular strength exercise was investigated in order to verify whether it would diminish cognitive alterations and modify the antioxidant intracellular scenery in an animal neuroinflammatory model in of the CA1 region of the hippocampus. Methods The animals received muscular strength training (SE) three ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Previous extensive literature indicates that the cells are constantly exposed to ROS whose increase above a given level results in oxidative stress [ 33 ]. Exposure to H 2 O 2 triggers a rise of ROS above basal levels that causes damage in cells [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous extensive literature indicates that the cells are constantly exposed to ROS whose increase above a given level results in oxidative stress [ 33 ]. Exposure to H 2 O 2 triggers a rise of ROS above basal levels that causes damage in cells [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As it is well known, oxidative stress is involved in the induction of apoptosis [ 35 ] and several studies have reported that the overproduction of ROS causes apoptosis [ 33 , 35 , 36 ]. Notably, NLX in our study reduced apoptotic cells at both of the concentrations examined in the presence of H 2 O 2 exposure.…”
Section: Discussionmentioning
confidence: 99%